2016
DOI: 10.1002/cmr.a.21397
|View full text |Cite
|
Sign up to set email alerts
|

Bloch equations for proton exchange reactions in an aqueous solution

Abstract: The extension of the Bloch equations for acid-base reactions in an aqueous solution is revisited. The acid-base reactions are second-order, and several reactions catalyzed by distinct catalysts may happen simultaneously. By constructing pseudo first-order reactions and assuming fast dissemination of protons from catalysts to solvent water, this extension converges to the well-known Bloch-McConnell equations for a two-site first-order exchange. Thus, explicit relationships between the parameters appearing in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…28 Varying pH using a phosphate buffer had no measurable effect on the measured exchange rate of the samples (Figures 5 and S3). However, a recent study suggests that creatine exchange is not strongly catalysed by phosphate, 29 and another study has shown a complex relationship between line broadening and phosphate, 30 which is similar to the changes we see in our data, as demonstrated in Figure S3c.…”
Section: Creatine Phantomsupporting
confidence: 92%
“…28 Varying pH using a phosphate buffer had no measurable effect on the measured exchange rate of the samples (Figures 5 and S3). However, a recent study suggests that creatine exchange is not strongly catalysed by phosphate, 29 and another study has shown a complex relationship between line broadening and phosphate, 30 which is similar to the changes we see in our data, as demonstrated in Figure S3c.…”
Section: Creatine Phantomsupporting
confidence: 92%
“…As evidenced by Figure 2d from the absence of a peak at ~1.25 ppm that is characteristic of Boc groups, the deprotection was almost quantitatively completed, giving the corresponding polymeric catalysts with different unit ratios in good yields (>85%). It is worth mentioning that the signal from amide N–H was not detected as a consequence of the proton exchange with trace water in the deuterated solvent [31,32].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the model can be extended to reactive mixtures, for which flow effects are hard to handle using calibration techniques. This can be done by incorporating the corresponding additional exchange terms in the Bloch equation [38].…”
Section: Mixtures Of Water + Acetonitrilementioning
confidence: 99%